Pengembangan Sosial Emosional Anak Usia Dini melalui Model Inside Outside Circle (IOC) - Hofifah (Lembaga Penelitian dan Pengabdian Institut Kariman Wirayudha Sumenep, 2023)
The purpose of this research is to investigate the social-emotional development of young children through the Inside Outside Circle (IOC) Model at TK Al-Qur'an Yayasan Abdullah 2 Gadding Sumenep. The type of research used is Classroom Action Research, and data collection tools consist of observation, interviews, and documentation. The analysis of classroom action research data is conducted in a series of steps with several cycles, where each cycle consists of four stages: planning, action implementation, observation, and reflection. Each cycle is conducted in one meeting. Data analysis employs a descriptive narrative approach. Based on the data analysis and discussion in Cycles I and II, it can be concluded that the Inside Outside Circle (IOC) Model can foster children's social-emotional development in Group A at TK Al-Qur'an YAS'A 2 Gadding Sumenep. This can be observed from the improvement in each cycle, where students who have developed very well (BSB) and developed as expected (BSH) in Cycle I reached 41%, while in Cycle II, those who developed very well (BSB) and developed as expected (BSH) reached 84%.